Atmosphere control and secondary phase migration during moderate-temperature sintering of aluminum nitride. Issue 11 (1st June 2022) - Rauchenecker, Johannes; Schwarz, Sabine; Artner, Werner; Konegger, Thomas
Abstract: Microstructure and thermal properties of aluminum nitride ceramics are strongly affected by sintering conditions. Reducing sintering environments, which are typically encountered during liquid-phase sintering of aluminum nitride in graphite furnaces, have a particular impact on the distribution of secondary phase and properties in the final ceramic part. In order to gain a deeper understanding of the effect of the sintering atmosphere, a systematic study of sintering conditions during consolidation of aluminum nitride ceramics at 1700 °C containing calcium oxide and yttrium oxide as sintering additives was carried out, varying carbon content in the sintering environment as well as nitrogen partial pressure. Compositional and microstructural changes were clarified employing electron microscopy techniques as well as phase and mass loss analysis. An increased migration of the secondary phase in the presence of reducing species was observed, resulting in a significant change in microstructural evolution, which was shown to affect mechanical as well as thermal properties of the resulting materials. Based on these findings, suitable sintering parameters for aluminum nitride ceramics leading toward consistent reducing conditions are proposed, resulting in materials with a flexural strength of 390 MPa and thermal conductivity of up to 175 W m - 1 K −1 . Thus, a robust framework for generating materials with well-controllable properties, an essential prerequisite for current and future applications of aluminum nitride in the field of thermal management, is provided.